Three-year effects of neighborhood social network intervention on mental and physical health of older adults. (2nd December 2021) - Harada, Kazuhiro; Masumoto, Kouhei; Katagiri, Keiko; Fukuzawa, Ai; Touyama, Michiko; Sonoda, Daichi; Chogahara, Makoto; Kondo, Narihiko; Okada, Shuichi
Abstract: Objectives: Although neighborhood is considered to be a crucial source of social network to promote health among older adults, current findings are mostly derived from observational study designs. This study examined whether participations in event-based community programs could increase neighborhood social network and whether such increase could lead to desirable changes in mental and physical health among older adults. Method: This study employed quasi-experimental design. A baseline questionnaire survey was sent to residents of Tsurukabuto community aged 60 years or more ( n  = 1769); 1, 068 responded. Community events were implemented approximately once a month for three years. Then, a three-year follow-up survey questionnaire was sent to the respondents of the baseline survey. The total number of respondents in the latter survey was 662; of the total, 173 participated in the intervention. Strong and weak ties with neighbors, mental well-being (Ikigai-9), health-related quality of life (HRQOL), and instrumental activity of daily living (IADL) were measured in the surveys. Results: The path analysis revealed that intervention participation was significantly associated with changes in strong ties (standardized path coefficient = 0.12) and changes in strong ties were associated with those in Ikigai-9 scores (standardized path coefficient = 0.15). The total and indirect effects of intervention participation on Ikigai-9 scores were significant. Significant intervention effects were not observed for HRQOL and IADL scores. Conclusion: This study found that participation in our event-based intervention could indirectly and positively influence older adults' mental well-being through their strong ties with their neighbors.